Phenomenological Study of The Deaf Community in Sign Language and The Meaning Construction By Alfred Schultz - Teguh Hidayatul Rachmad; Yohanes Probo Dwisasongko (Journal of Content and Engagement, 2025)
Every event that presents itself in society and shapes a habit is a way that can be brought forth to draw a meaning. Through the actions carried out by those who have hearing limitations, especially the deaf, their ways and actions make interpersonal communication forms intriguing to be deeply examined. With all their forms and limitations, spaces of communication always manifest and are given their meanings. The way the deaf community communicates, whether through sign language or alternative methods, highlights the richness of their social interactions and the unique construction of meaning that occurs in these interactions. Meaning in this context is not fixed, but rather fluid and dynamic, shaped by both individual and collective experiences. According to Alfred Schutz's phenomenological approach, meaning is a process that emerges from individuals’ lived experiences and their interactions with others. It is something that adapts to the conditions and contexts in which it is embedded. Schutz’s concept of “meaning construction” emphasizes that meaning is not only a subjective experience but also a social one, grounded in shared understanding.